2007
DOI: 10.1002/adfm.200600167
|View full text |Cite
|
Sign up to set email alerts
|

NCN‐Coordinated Platinum(II) Complexes as Phosphorescent Emitters in High‐Performance Organic Light‐Emitting Devices

Abstract: A series of terdentate cyclometallated PtII complexes with remarkable luminescence properties are used as new phosphorescence‐emitting dopants in a blended host matrix as the emitting layer, resulting in very high electroluminescence efficiencies. Because of the high phosphorescence quantum yields of these Pt complexes and the efficient energy transfer from both singlet and triplet excited states of the host to the emitting guest, external electroluminescence quantum efficiencies as high as 4–16 % photons per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
95
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(105 citation statements)
references
References 35 publications
(39 reference statements)
4
95
1
3
Order By: Relevance
“…8%). 33 On the other hand, the corresponding device comprising [PtL 6 -C^C-C 6 H 3 F 2 ] displays QE max z 12%. This value is about three times higher than that of a similarly constructed OLED with [PtL 6 Cl], 33 and more than an order of magnitude superior to OLEDs based on related C^N^N coordinated platinum complexes of 6-aryl-2,2 0 -bipyridines with phenylacetylide coligands, for which the EL QE decreases from 1.6% to 0.9% on going from a 2% to a 4% Pt-doped device.…”
Section: Oled Configurationsmentioning
confidence: 99%
See 1 more Smart Citation
“…8%). 33 On the other hand, the corresponding device comprising [PtL 6 -C^C-C 6 H 3 F 2 ] displays QE max z 12%. This value is about three times higher than that of a similarly constructed OLED with [PtL 6 Cl], 33 and more than an order of magnitude superior to OLEDs based on related C^N^N coordinated platinum complexes of 6-aryl-2,2 0 -bipyridines with phenylacetylide coligands, for which the EL QE decreases from 1.6% to 0.9% on going from a 2% to a 4% Pt-doped device.…”
Section: Oled Configurationsmentioning
confidence: 99%
“…33 On the other hand, the corresponding device comprising [PtL 6 -C^C-C 6 H 3 F 2 ] displays QE max z 12%. This value is about three times higher than that of a similarly constructed OLED with [PtL 6 Cl], 33 and more than an order of magnitude superior to OLEDs based on related C^N^N coordinated platinum complexes of 6-aryl-2,2 0 -bipyridines with phenylacetylide coligands, for which the EL QE decreases from 1.6% to 0.9% on going from a 2% to a 4% Pt-doped device. 14 The superiority of [PtL 6 -C^C-C 6 H 3 F 2 ] over [PtL 3 -C^C-C 6 H 3 F 2 ], despite the similarity of their solution photophysical and electrochemical properties, is likely to be due to inhibition of ''aggregate-induced quenching'', owing to the steric bulk of the mesityl group.…”
Section: Oled Configurationsmentioning
confidence: 99%
“…The emissive layer (EML) of the WLED reported here consists of a bluish-green emitting phosphor, selected from a group of highly efficient N C N-coordinated platinum(II) complex phosphors, platinum [methyl-3,5-di-(2-pyridyl) benzoate] chloride (PtL 2 Cl) electron acceptor, [11,12] and (4,4′,4″-tris(N-(3- Figure 1 shows the absorption and PL spectra of the two different composition EMLs and their material components. It is apparent that unlike the PL material component spectra, the emission from the EMLs shows up as the broad band spectra characteristic of triplet 3 PtL 2 Cl:PtL 2 Cl〉* excimers [13] and 3 m-MTDATA:PtL 2 Cl〉* exciplexes, [14] respectively.…”
mentioning
confidence: 99%
“…28 However, the effect of a π--delocalized electron--donating substituent on the cyclometallated 1,3--di(2--pyridyl)benzene ligand of such Pt(II) complexes has not been investigated from an NLO point of view. Such an investigation is appealing, because the absorption bands of this kind of complex are red shifted by increasing the donor ability of the substituent at the central 5--position of the cyclometallating ring, through stabilisation of charge transfer states, 29,30 and it is known that the presence of charge--transfer transitions at low energy can lead to a high quadratic hyperpolarizability. 31,32 In addition a recent EFISH study showed that trans-…”
Section: Introductionmentioning
confidence: 99%